Ancylis sederana Chrétien, 1915 a new species to the European fauna from Spain (Lepidoptera: Tortricidae) - F. Graf (SHILAP Revista de lepidopterología, 2019)
Ancylis sederana Chrétien, 1915 is for the first time reported from Europe. During an expedition in Southern Spain, the first author captured a female of this species near Almeria. This species is described from Northern Africa, Algeria (Biskra) and Tunisia (Gafsa). Furthermore was found they on Arabian Peninsula (Oman). The foodplant is Zizyphus lotus (L.) Lam. For the first time the female genital is imaged.